Immobilization of NTPDase-1 from Trypanosoma cruzi and Development of an Online Label-Free Assay - Felipe Antunes Calil; Juliana Maria Lima; Arthur Henrique Cavalcante de Oliveira; Christiane Mariotini-Moura; Juliana Lopes Rangel Fietto; Carmen Lucia Cardoso (Journal of Analytical Methods in Chemistry)
The use of IMERs (Immobilized Enzyme Reactors) as a stationary phase coupled to high performance chromatographic systems is an interesting approach in the screening of new ligands. In addition, IMERs offer many advantages over techniques that employ enzymes in solution. The enzyme nucleoside triphosphate diphosphohydrolase (NTPDase-1) from Trypanosoma cruzi acts as a pathogen infection facilitator, so it is a good target in the search for inhibitors. In this paper, immobilization of NTPDase-1 afforded ICERs (Immobilized Capillary Enzyme Reactors). A liquid chromatography method was developed and validated to monitor the ICER activity. The conditions for the application of these bioreactors were investigated, and excellent results were obtained. The enzyme was successfully immobilized, as attested by the catalytic activity detected in the TcNTPDase-1-ICER chromatographic system. Kinetic studies on the substrate ATP gave KM of 0.317 ± 0.044 mmol·L−1, which still presented high affinity compared to in solution. Besides that, the ICER was stable for 32 days, enough time to investigate samples of possible inhibitors, including especially the compound Suramin, that inhibited 51% the enzyme activity at 100 µmol·L−1, which is in accordance with the data for the enzyme in solution.